Linguistic Markers of Autism Spectrum Disorder in Narrative Production: Evidence From the Monkey Cartoon Storytelling Task of the Autism Diagnostic Observation Schedule - Eleni Peristeri; Katerina Drakoulaki; Antonia Boznou; Michaela Nerantzini; Spyridoula Varlokosta (Autism and Developmental Language Impairments)
Background and aims The Autism Diagnostic Observation Schedule (ADOS-2) is considered a “gold standard” diagnostic instrument in the assessment of autism spectrum disorder (ASD). The Monkey Cartoon task is an optional pictured storytelling task in ADOS-2, which has been designed to assess gestural and verbal communication in autistic children while telling a story. It is well established that storytelling is challenging for autistic children, particularly for the content and coherent organization of the story, also known as narrative macrostructure. Existing evidence on the efficacy of the Monkey Cartoon task to pinpoint differences between autistic and neurotypical individuals in narrative macrostructure is scant. In this study, we used a version of the Monkey Cartoon task with modified scoring to analyze the narrative macrostructural skills of two groups of children with and without ASD. We also investigated the relations between narrative macrostructure and language ability in each group. Methods A group of 16 Greek-speaking autistic children and 16 age- and IQ-matched neurotypical children were administered the Monkey Cartoon storytelling task. Children's vocabulary and syntactic skills were also measured. Narratives were analyzed in terms of macrostructural features, including story completeness and story grammar, as well as units denoting the setting, internal responses and added details. Results The autistic children had lower scores in communicating the story content rather than story grammar. Moreover, the autistic group tended to include less information on the story's setting and more off-topic utterances than their neurotypical peers. Regarding the relations between narrative macrostructure and language ability, the two groups dissociated since the autistic children tended to rely on vocabulary at the expense of including irrelevant information in their narratives, while neurotypical children relied on both lexical and syntactic skills, especially when instantiating references to the story characters’ mental states and the setting of the story, respectively. Conclusions The Monkey Cartoon storytelling task seems to be efficient at revealing pragmatic weaknesses mainly at the thematic content level in autistic children. Also, the frequent use of semantically- and pragmatically-irrelevant information in storytelling differentiated autistic from neurotypical children, and may thus be treated as a distinguishing feature of ASD in narrative production. Implications The findings demonstrate the viability of the Monkey Cartoon task in highlighting language markers of ASD in narrative macrostructure, with clinical implications for enhancing clinical practice in countries like Greece that face a shortage of narrative assessment tools for autistic children.